2016
DOI: 10.1016/j.immuni.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Engineered CAR T Cells Targeting the Cancer-Associated Tn-Glycoform of the Membrane Mucin MUC1 Control Adenocarcinoma

Abstract: SUMMARY Genetically modified T cells expressing chimeric antigen receptors (CARs) demonstrate robust responses against lineage restricted, non-essential targets in hematologic cancers. However, in solid tumors, the full potential of CAR T cell therapy is limited by the availability of cell surface antigens with sufficient cancer-specific expression. The majority of CAR targets have been normal self-antigens on dispensable hematopoietic tissues or overexpressed shared antigens. Here, we established that abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
343
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 495 publications
(391 citation statements)
references
References 49 publications
9
343
0
2
Order By: Relevance
“…Therefore, tumor-specific CAR targets need to be selected. Posey et al reported a CAR that targets an abnormal glycoform of MUC1, Tn-MUC1, which is specifically expressed by multiple types of tumors but not on the cellular surface of normal human tissues [74] . Thus, this approach allowed the selection of aberrantly glycosylated antigens and constitutes a safer alternative to tumor-associated antigens for CAR-based therapy.…”
Section: Improvements In Safetymentioning
confidence: 99%
“…Therefore, tumor-specific CAR targets need to be selected. Posey et al reported a CAR that targets an abnormal glycoform of MUC1, Tn-MUC1, which is specifically expressed by multiple types of tumors but not on the cellular surface of normal human tissues [74] . Thus, this approach allowed the selection of aberrantly glycosylated antigens and constitutes a safer alternative to tumor-associated antigens for CAR-based therapy.…”
Section: Improvements In Safetymentioning
confidence: 99%
“…Targeting against the tumor antigen mesothelin [51, 52], carcinoembryonic antigen [53], prostate stem cell antigen [54, 55], HER2 neu, CD24 [56], CD133 and mucin-1 (MUC-1) [57] has shown activity in preclinical tumor models. Currently, multiple clinical phase I and II trials using CAR T-cell therapy targeting prostate stem cell antigen (e.g.…”
Section: Adoptive T-cell Therapymentioning
confidence: 99%
“…Although most CAR targets have been limited to natural cell-surface antigens in the form of proteins, it is possible to target post-translational modifications of proteins 26,27 and glycosphingolipids with CARs. 28 T cells can also be genetically modified with natural or engineered T cell receptors (TCRs), which recognize peptides presented in the context of major histocompatibility complex (MHC).…”
Section: Potential Mechanisms Of Toxicity Of Car T Cellsmentioning
confidence: 99%